Safety and Efficacy of Pneumococcal Vaccination in Pediatric Nephrotic Syndrome - Goonewardene, Shamitha Thishakya; Tang, Calyn; Tan, Loh Teng-Hern; Chan, Kok-Gan; Lingham, Prithvy; Lee, Learn-Han; Goh, Bey-Hing; Pusparajah, Priyia (Frontiers in Pediatrics, 2019)
Nephrotic syndrome affects both children and adults. Idiopathic nephrotic syndrome is reported to be the most frequent renal pathology in childhood. Nephrotic children are high at risk for severe pneumococcal infections as one of the life-threatening complications of nephrotic syndrome due to involvement of the immunosuppressive regimen and the acquired immune deficiency induced by nephrotic syndrome including decreased plasma IgG and low complement system components. Aiming to prevent pneumococcal infection is of paramount importance especially in this era of ever increasing pneumococcal resistance to penicillins and cephalosporins. The pneumococcal vaccines currently available are inactivated vaccines; the two main forms in use are polysaccharide vaccines and conjugated vaccines. However, the data supporting the use of these vaccines and to guide the timing and dosage recommendations is still limited for nephrotic children. Thus, this review discusses the evidences of immunogenicity and safety profile of both vaccinations on nephrotic patients as well as the effect of nephrotic syndrome treatment on vaccine seroresponses.